Gabon : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2020)
Since the approval of the first RFI request on April 9, 2020 (IMF Country Report No 20/109), weaker external demand and a more pronounced impact of containment measures have further deteriorated growth prospects and worsened external and fiscal positions. The authorities are requesting a purchase under the Rapid Financing Instrument (RFI) of 50 percent of quota (SDR 108 million) to be used as budget support to help address urgent balance of payment (BoP) needs and mitigate the risk of disorderly fiscal or BoP adjustment. This additional request will bring the total purchases under the RFI to 100 percent of quota in 2020.